Dynamic Analysis of Concrete Rectangular Tanks Considering the Effect of Soil-Structure-Fluid Interaction - Mehrdad Khoubani (Iranian Society of Structrual Engineering (ISSE), 2018)
In this paper, the dynamic behavior of concrete rectangular tanks under the effects of soil-structure interaction and motion caused by earthquakes is studied. The simultaneous effects of soil-structure-fluid interaction on the dynamic behavior of concrete rectangular tanks by the finite element method in three-dimensional space, based on linear analysis and in-time domain is discussed. Considering that, in some tanks such as large reinforced concrete pool structures used for long-term storage of nuclear spent fuel assemblies or prestressed concrete water tanks where the flexibility of the rectangular tank wall can cause a significant effect on the dynamic responses, the tank walls are considered as flexible plates. A simple model with a viscous boundary is used to include deformable foundation effects as a linear elastic medium. For dynamic evaluation of a rectangular container located on the foundation, six different types of soil approved by the current regulations and design standards are used. In the finite element model, the effects of different soil types on structural responses have been evaluated and comparisons between dynamic responses such as base shear, base moment, hydrodynamic pressure distribution and sloshing responses under different ground motions have been evaluated by changing soil properties. It is concluded that the soil under the tank, depending on its type, can cause significant changes in the dynamic responses.